2018
DOI: 10.1007/s11150-018-9421-5
|View full text |Cite
|
Sign up to set email alerts
|

Occupational segregation by sexual orientation in the U.S.: exploring its economic effects on same-sex couples

Abstract: This paper examines the importance of the occupational sorting of individuals in same-sex couples in explaining the economic position of lesbian women and gay men beyond controlling for occupation in the estimation of their respective wage gaps, as usually done in the literature. The analysis reveals that the distribution of partnered gay men across occupations brings them a monetary gain, with respect to the average wage of coupled workers, whereas the occupational sorting of partnered lesbian women only allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Using common predictors of voter turnout, such as educational attainment, income or place of residence, in a matching model is not advisable due to the so‐called ‘bad control problem’ (Angrist & Pischke, 2009). These attributes are all ‘post‐treatment’ and can be influenced, at least in part, by the treatment variable (Antecol et al., 2008; Fine, 2015; Poston et al., 2017; Río & Alonso‐Villar, 2019). As a matter of consequence, their inclusion might dilute the impact of sexuality on voter turnout.…”
Section: Methodsmentioning
confidence: 99%
“…Using common predictors of voter turnout, such as educational attainment, income or place of residence, in a matching model is not advisable due to the so‐called ‘bad control problem’ (Angrist & Pischke, 2009). These attributes are all ‘post‐treatment’ and can be influenced, at least in part, by the treatment variable (Antecol et al., 2008; Fine, 2015; Poston et al., 2017; Río & Alonso‐Villar, 2019). As a matter of consequence, their inclusion might dilute the impact of sexuality on voter turnout.…”
Section: Methodsmentioning
confidence: 99%
“…For example, stigma and discrimination appears to motivate sexual minorities to complete more college but with college majors comprised of more tolerant individuals even if they map into lower paying occupations (Burn & Martell, 2020 ). The lack of access to the rights and privileges that accompany marriage may lower the returns to investments in household assets thereby influencing labor market attachment and occupational attainment (Del Río & Alonso-Villar, 2019 ; Hansen et al, 2020 ). Indeed, such behavior has long been argued as an explanation of the marriage premium observed among heterosexual men (Loh, 1996 ) and more recently among men and women in same-sex marriages (Martell & Nash, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is strong evidence that occupational segregation explains a large part of the gender wage gap and the racial wage gap (Blau and Kahn ; Cotter, Hermsen, and Vanneman ; Petersen and Morgan ), which suggests that occupations may be important in explaining the earnings of the various sexual orientation–gender–race groups. Thus, distinguishing among 453 occupational categories, Del Río and Alonso‐Villar () showed that occupational sorting plays an important role in explaining the earnings differentials between homosexual and heterosexual workers. The higher educational achievement of gay men and lesbians makes it possible for them to access highly paid occupations, especially gay men, which results in earnings that are higher than those of their straight peers.…”
Section: Literature Review: Wages and Occupationsmentioning
confidence: 99%
“…The magnitude of segregation by sexual orientation has been recently quantified. Using a fine occupational classification and distinguishing among four groups—women and men living in same‐sex and different‐sex couples—Del Río and Alonso‐Villar () showed that partnered lesbians in the United States are the most evenly distributed group across occupations whereas their straight counterparts represent the group most unevenly distributed (i.e., it is the group experiencing more overrepresentation in some occupations and underrepresentation in others). The levels of unevenness for gay and heterosexual men, which are similar to one another, are between the levels for lesbian and heterosexual women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation